2016
DOI: 10.1021/acs.est.5b04795
|View full text |Cite
|
Sign up to set email alerts
|

Crossing the Border between Laboratory and Field: Bacterial Quorum Quenching for Anti-Biofouling Strategy in an MBR

Abstract: Quorum quenching (QQ) has recently been acknowledged to be a sustainable antifouling strategy and has been investigated widely using lab-scale membrane bioreactor (MBR) systems. This study attempted to bring this QQ-MBR closer to potential practical application. Two types of pilot-scale QQ-MBRs with QQ bacteria entrapping beads (QQ-beads) were installed and run at a wastewater treatment plant, feeding real municipal wastewater to test the systems' effectiveness for membrane fouling control and thus the amount … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
84
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 134 publications
(106 citation statements)
references
References 45 publications
2
84
0
Order By: Relevance
“…Recently a novel method, termed quorum quenching (QQ), has been demonstrated to reduce membrane biofouling and to repress the virulence factors of some pathogens by blocking the ability of communication in bacteria [80,81,82,83]. Likewise, the basis behind the QQ approach as a means to limit SRB is based on the assumption that interference of the communication channels would reduce biofilm formation and the associated metabolism of SRBs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently a novel method, termed quorum quenching (QQ), has been demonstrated to reduce membrane biofouling and to repress the virulence factors of some pathogens by blocking the ability of communication in bacteria [80,81,82,83]. Likewise, the basis behind the QQ approach as a means to limit SRB is based on the assumption that interference of the communication channels would reduce biofilm formation and the associated metabolism of SRBs.…”
Section: Introductionmentioning
confidence: 99%
“…A corresponding improvement in the water flux and decrease in biofilm thickness were observed. A recent study involving pilot-scale MBRs (i.e., closed reactor systems) that were operated for at least four months to treat real-strength municipal wastewater [119,120] also showed that QQ was able to delay transmembrane pressure build-up and reduce EPS concentrations in membrane biofilms [83]. Although similar demonstrations of QQ to reduce SRBs are not available, these findings collectively show the potential of a QQ approach to delay the biofilm formation process and hence avoid the consequential effect of biocorrosion in a contained system (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Yeon et al [24] were the first to provide evidence of the occurrence of AHL-mediated QS in MBRs by proving the presence of different AHLs in the biocake formed on the membrane surface. This result has been confirmed [25,26,27,28,29,30] and then taken to the next step with the determination of a correlation between the AHL amount and the transmembrane pressure (TMP) level [24,29]. Hence, the occurrence of AHL-mediated QS has not only been highlighted but has also been demonstrated to be closely related to biofouling in MBRs.…”
Section: Introductionmentioning
confidence: 78%
“…Kim et al [50] further developed macrocapsules by coating the CEBs with a microporous polymer layer for better resistance to harsh conditions resulting from the use of real WW. Recently, Lee et al [26] developed QQ beads made of a mixture of polyvinyl alcohol and sodium alginate to reinforce their stability in real WW. The beads were then inserted into the MBR where they could move freely.…”
Section: Methods For Entrapping Qq Bacteria In Mbrsmentioning
confidence: 99%
“…These results suggest that quorum sensing has a positive effect on wastewater treatment. However, quorum sensing has also been associated with the formation of membrane biofouling in a membrane bioreactor system [7]. In this case, inhibition of quorum sensing was an effective strategy to control membrane biofouling [7].…”
Section: Introductionmentioning
confidence: 99%